Removal of triclosan from water by sepiolite supported bimetallic Fe/Ni nanoparticles. Issue 21 (19th September 2022) - Ren, Guofa; Shi, Yichao; Cai, Yunmei; Yuan, Lingling; Wu, Kangming; Ouyang, Minghui; Zheng, Kewen
ABSTRACT: A simple and low-cost route to fabricate sepiolite-supported bimetallic Fe/Ni (Sep-Fe/Ni) nanoparticles was obtained by synchronous liquid phase reduction method. The as prepared composite was used to remove triclosan (TCS) from aqueous solutions. X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and Brunauer-Emmett-Teller (BET) analysis were used for characterization of the materials. As the supporting material, Sep dispersed Fe/Ni nanoparticles on its surface effectively and reduced the agglomeration phenomenon, providing more reactive sites. Sep-Fe/Ni had a large surface area of 90.5 m 2 /g, which was considerably higher than that of Fe/Ni (9.2 m 2 /g). Sep-Fe/Ni exhibited an enhanced TCS removal efficiency, as compared to the Fe/Ni and Sep materials. Operation factors, including the solution pH, initial TCS concentration, and material dosage, were investigated and found to be influential for TCS removal. The kinetic analysis indicated that the depletion of TCS in aqueous solutions conformed to the pseudo-first-order kinetic model under optimized conditions. The transformation pathway of TCS was studied in detail, revealing that the dechlorination of TCS by Sep-Fe/Ni is a stepwise reaction, namely from TCS to di-chlorinated intermediates, with the newly formed intermediate products also degrading into mono-chlorinated products by further reductive dechlorination. This study demonstrated that Sep-Fe/Ni is a promising reductant for TCS removal in water. GRAPHICAL ABSTRACT: UF0001